POST AMPUTATION RESPONSE AND COPING OF DIABETES MELLITUS PATIENT IN ULIN GENERAL HOSPITAL BANJARMASIN - Candra Kusuma Negara (Journal of Nursing Science Update (JNSU), 2017)
DM disease is a health problem that is very important because it is associated with a high incidence of complications and high mortality. For most people the disease diabetes mellitus is a disease that is very worrying and the public aware of the magnitude of the potential dangers caused. For individuals who suffer from diabetes mellitus with post-amputation, the next life is a new round of challenges and changes, and will go through the process of coping with the change process. The  aim of this study was to explore various diabetic patients post-amputation responses and coping experienced. This study used a qualitative phenomenological study. Retrieving data using in depth interview in four participants were treated at Diabetic Foot Polyclinic Ulin General Hospital Banjarmasin equipped with a guidance interview and informed consent. The analytical method structure from Creswell into 6 steps. There are 2 theme depicting various responses post-amputation and   depicting various coping DM patients post-amputation. Sub-Theme in depicting various responses post-amputation namely: (1) Experiencing physical barriers, (2) Experiencing the changing role, (3) Experiencing the grieving process, and are 4 Sub-theme depicting various coping DM patients post-amputation namely: (1) More worship, (2) Accept the circumstances, (3) A strong Motivation, (4) social support.